Research on IMS Core Network Security Index System - Qingnian Chen; Haoming Ou (Dianxin kexue)
The establishment of an evaluation model of quantitatively assessing IMS network security was discussed, and an example about the evaluation process was given. The proposed network security assessment system could also be used to assess soft switch, mobile core network, and so on.